Exploring Mosston’s Spectrum of Teaching Styles usage and perception among student teachers of Sultan Idris Education University - Jeganathan, Sanmuga Nathan K.; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study aimed to explore sports science student teacher’s (n =100), usage and perceptions of Mosston’s Spectrum of Teaching Styles. The study adopted a qualitative approach of document analyses to investigate the predominant styles used by the student teachers during their teaching practical session in schools. This research, too employed a survey to explore their perceptions about the different teaching styles. The finding revealed 46% student teachers’ lesson predominantly used style B (practice style), followed by 38% style A (command style) especially in teaching fitness topics in their practical teaching session. Findings indicated there were significant differences in perception of using 11 different teaching styles where F(10,1089) = 13.67, p< 0.05, indicated style B was the most perceived teaching style followed by style H (divergent production style) and style F (guided discovery style) among student teachers. Finding indicated only style G (convergent discovery style) was significantly favoured by female student teachers (4.27±1.52) compared to male counterparts (3.81±.82), F(1,98)= 3.91, p <0.05. The findings revealed that there were no significant differences in perceptions between reproduction (teacher-centered) and production (learner-centerd) cluster of teaching styles, t = (1098) =-.396, p> 0.05. In conclusion, more effort had to be done in Malaysia to develop more holistic pedagogical styles